IMPLEMENTASI AKAD ISTISHNA’ PADA PEMESANAN PAKAIAN DI GARMEN AL-ZAYTUN - Fitria, Annisa; Rojak Samsudin, Agus; Aminulloh, Ali (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
Abstract: The purpose of this study is to examine the implementation of the Istishna' contract in clothing orders at Al-Zaytun Garment, the legal principles of sale and purchase in the Istishna' contract, and the practice of ordering clothing at Al-Zaytun Garment. This research employs a qualitative approach with field research as its type. Data collection was carried out through field observations, documentation, and in-depth interviews with the field coordinator of Al-Zaytun Garment and several employees involved in the clothing ordering process. The research findings indicate that the ordering process at Al-Zaytun Garment operates under strict internal controls. The process involves several stages, starting from placing the order to the retrieval of the finished goods. The implementation of the Istishna' contract in the ordering process follows Sharia principles, ensuring clarity between the buyer and the seller, where the garment staff is responsible for fulfilling the order criteria, while the buyer specifies the criteria and makes the payment. Keywords: Istishna' contract, ordering, clothing, Garment